Starość jako etap życia i jego potrzeby - Dziendziura, Małgorzata (Studia Edukacyjne, 2024)
Globally, we have witnessed a trend of increasing human lifespan, and the rate at which societies are aging is much faster now than in the past. Old age, as a new phase of human life, brings with it new challenges, needs, and opportunities. Meeting the needs of the elderly requires support from family, local communities, and the state. Looking at old age through the lens of its many dimensions (biological, psychological, and social), identifying and understanding the needs that arise from it, and implementing appropriate solutions is crucial to changing our perception of aging and building a society that can support the elderly.